Women’s Activism in the Printed Media of the Dutch East Indies: Between Progressive Narratives and the Adaptation of Traditional Roles in Health and Education Issues, 1930–1935 - Haghia, Raisye Soleh; Widyakinasih, Rara Rastri; Setyaningsih, Laras; Sari, Noor Fatia Lastika (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article examines the construction of Indigenous women’s identities in the Dutch East Indies press between 1930 and 1935, focusing on two central issues that preoccupied women at the time: education and health. The implementation of the Ethical Policy heightened women’s awareness of their place within colonial society, prompting them to articulate their ideas through the printed media. Among the most significant platforms were Sedar and Pedoman Isteri. This study investigates how these publications represented women’s roles and positions in relation to education and health, and argues that—despite stemming from distinct ideological orientations—both played equally vital roles in advancing Indonesian women’s causes. By employing historical methods and qualitative analysis of primary sources, particularly articles from Sedar and Pedoman Isteri, this research adopts Judith Butler’s gender performativity framework to interpret the findings. The analysis reveals that Sedar, as a progressive outlet, emphasized education as a pathway to liberating women from patriarchal structures, while Pedoman Isteri reinforced domestic roles through narratives on health and family welfare. Rather than negating one another, these approaches reflect the diversity of strategies women employed to negotiate their place in the colonial public sphere. The study underscores that the colonial press functioned as a crucial arena for women to shape and contest their identities, and demonstrates that women’s historical agency was multiple and complex, rather than singular. By tracing these dynamics, this research offers a historical lens through which to understand the enduring struggles over women’s access to education and health in Indonesia today.